Sodobne migracije in dileme varnosti - Medica, Karmen (Socialno delo, 2007)
Migrations, which contribute to the development of the so-called developed world and to the formation of multi-cultural societies, are imposed on the poor and a choice only for the elite. The immigrantsć positions depend on how,whence and when they arrive. Neither the countries open to influx nor those enforcing strict immigration controls have yet found a solution to restrict illegal entry, residence and work. The notion of the free flow of people is becoming dubitable even within the EU itself. The political arguments of security, as well as the imagery of global threat, function largely as everyday defensive games. The perpetual question raised by the official circles and the media is how safe we really are from illegal migrants. But the opposite might be asked as well: how safe are illegal migrants from Europe''s need of fresh labour, its low birth rate, and its desire for faster gains?
Keywords: human migration; migracije; legalnost; security; varnost; Slovenia; Slovenija; Europe; Evropa